Aluminum titanium phosphate and preparation method thereof and aluminum titanium phosphate lithium electrolyte material

Through the co-precipitation reaction and spray drying process of trivalent titanium and trivalent aluminum with ascorbic acid, aluminium titanium phosphate with high density and uniform particle size was prepared, which solved the problem of difficult control of the particle size and specific surface area of ​​the material in the prior art. Improves the performance of lithium-ion batteries.

CN118458723BActive Publication Date: 2025-01-10HUBEI WANRUN NEW ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410511387.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-25
Publication Date
2025-01-10
Estimated Expiration
2044-04-25

AI Technical Summary

Technical Problem

It is difficult to obtain materials with a small primary particle size and a small specific surface area in the prior art, which affects the conductivity and cyclic stability of lithium-ion batteries.

Method used

The co-precipitation reaction of trivalent titanium and trivalent aluminum with ascorbic acid is adopted to prepare aluminum titanium phosphate by spray drying and high-temperature calcination, controlling the particle size and specific surface area, avoiding segregation, and achieving high density products.

Benefits of technology

Titanium aluminum phosphate with a primary particle size of 100-300 nm and a BET of 4.0-5.0 m2/g was successfully prepared, which improved the conductivity and electrochemical stability of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118458723B_ABST
    Figure CN118458723B_ABST
Patent Text Reader

Abstract

The present application provides a kind of aluminum titanium phosphate and its preparation method and aluminum titanium phosphate lithium electrolyte material, belonging to the field of solid electrolyte precursor preparation, wherein the preparation method of aluminum titanium phosphate includes: preparing a mixed solution of trivalent titanium source, trivalent aluminum source and ascorbic acid; adjusting the pH of the mixed solution to 6.5-7.5 to obtain titanium aluminum hydroxide; spray drying the titanium aluminum hydroxide, phosphorus source and water to obtain an intermediate product; calcining the intermediate product to obtain aluminum titanium phosphate. The present application prepares titanium aluminum hydroxide with uniform particle size by coprecipitation, and then prepares aluminum titanium phosphate by solid phase sintering method, which is conducive to obtaining an aluminum titanium phosphate precursor with a small primary particle size and a small specific surface area.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solid electrolyte precursor preparation, and in particular to aluminum titanium phosphate and a preparation method thereof, and an aluminum titanium phosphate lithium electrolyte material. Background Art

[0002] Lithium-ion battery is a secondary battery (rechargeable battery) that mainly relies on the movement of lithium ions between the positive and negative electrodes to work. + Insertion and deinsertion back and forth between the two electrodes: During charging, Li + It is deintercalated from the positive electrode and intercalated into the negative electrode through the electrolyte, and the negative electrode is in a lithium-rich state; the opposite is true during discharge.

[0003] With the rapid development of new energy vehicles and energy storage, lithium-ion power batteries are developing rapidly. Solid-state batteries are a type of battery technology. Unlike the lithium-ion batteries and lithium-ion polymer batteries commonly used today, solid-state batteries are batteries that use solid electrodes and solid electrolytes. Since the scientific community believes that lithium-ion batteries have reached their limits, solid-state batteries have been seen in recent years as batteries that can inherit the status of lithium-ion batteries. Solid-state lithium battery technology uses glass compounds made of lithium and sodium as conductive materials to replace the electrolyte of previous lithium batteries, greatly improving the energy density of lithium batteries.

[0004] The solid electrolytes used in solid-state batteries include oxides, sulfides, polymers, etc., as well as NASICON-type lithium aluminum titanium phosphate. Lithium aluminum titanium phosphate solid electrolytes have good chemical stability, especially high voltage stability and chemical stability in the air, and the ionic conductivity can also reach an acceptable level in practicality. It has broad application prospects in the field of lithium-ion batteries.

[0005] The primary particle size of common lithium aluminum titanium phosphate is 100-300nm, and the BET is 2.5-5.5m 2 / g, which requires its precursor titanium aluminum phosphate to have a smaller primary particle size and a smaller BET. However, these two are generally contradictory. How to ensure that titanium aluminum phosphate has a smaller BET at a smaller primary particle size has become a problem that needs to be solved urgently. Summary of the invention

[0006] In view of the technical problems existing in the background technology, the present application provides a titanium aluminum phosphate and a preparation method thereof and a titanium aluminum phosphate lithium electrolyte material, aiming to solve the technical problem that the existing method is difficult to obtain titanium aluminum phosphate with both a smaller primary particle size and a smaller BET.

[0007] In a first aspect, the present invention provides a method for preparing aluminum titanium phosphate, comprising the following steps:

[0008] preparing a mixed solution of a trivalent titanium source, a trivalent aluminum source and ascorbic acid;

[0009] Adjusting the pH of the mixed solution to 6.5-7.5 to obtain titanium aluminum hydroxide;

[0010] The titanium aluminum hydroxide, phosphorus source and water are mixed and then spray-dried to obtain an intermediate product;

[0011] The intermediate product is calcined to obtain aluminum titanium phosphate.

[0012] In the technical solution of the embodiment of the present application, trivalent aluminum ions, trivalent titanium ions and ascorbic acid are first mixed to undergo a co-precipitation reaction, then spray-dried to coat the phosphorus source, and finally calcined at a high temperature to obtain aluminum titanium phosphate, which not only has a smaller primary particle size but also a smaller specific surface area.

[0013] In some embodiments, the trivalent titanium source is one or more of titanium trichloride, titanium sulfate, and titanium oxychloride; the trivalent aluminum source is one or more of aluminum trichloride, aluminum sulfate, and aluminum nitrate; the molar ratio of the trivalent titanium source, the trivalent aluminum source, and ascorbic acid is (1.65-1.75): (0.2-0.4): (0.01-0.05).

[0014] In this embodiment, trivalent aluminum ions and trivalent titanium ions are mixed, and the addition of ascorbic acid avoids the oxidation of trivalent titanium ions, making it easier to control the precipitation rate, avoid segregation, achieve co-precipitation of titanium and aluminum, and thus prepare titanium aluminum hydroxide with a smaller primary particle size and more uniform precipitation.

[0015] In some embodiments, alkali solution is added to the mixed solution to adjust the pH of the mixed solution to 6.5-7.5; and / or the temperature of the mixed solution is 40-60°C; and / or the alkali solution is added for 30-120 min; and / or after the alkali solution is added, the reaction is continued for 30-60 min.

[0016] In this embodiment, by controlling the addition conditions of the alkali solution, the temperature of the solution, and the reaction time, uniform mixing and precipitation of titanium and aluminum during the coprecipitation reaction are facilitated, thereby avoiding the segregation problem of aluminum and titanium.

[0017] In some embodiments, the alkali solution is ammonia water, and the concentration of the ammonia water is 2-4 mol / L.

[0018] The solubility product of the precipitation reaction is small, the solution supersaturation is large, the nucleation rate is too large, and flocculent solids are easily formed. Therefore, in this embodiment, ammonia water is added during the reaction process to act as both a pH regulator and a complexing agent. The ammonia ions in the ammonia water will undergo a complex reaction with the metal ions in the co-precipitation product, thereby promoting the formation and stability of the precipitate while forming the precipitate. At the same time, ammonia water also has the function of a nucleating agent, which reduces the supersaturation and nucleation rate to a certain extent, so that the nucleation rate is dynamically balanced with the crystal growth rate, thereby facilitating the acquisition of titanium aluminum hydroxide with a small primary particle size and high density.

[0019] In some embodiments, before mixing the titanium aluminum hydroxide, the phosphorus source and water, the method further comprises washing the titanium aluminum hydroxide until the conductivity of the washing water is ≤150 μS / cm.

[0020] In this embodiment, by washing the titanium aluminum hydroxide, the excess ions that do not participate in the reaction in the precipitate can be removed, thereby effectively avoiding the influence of these ions on the final form of subsequent products.

[0021] In some embodiments, titanium aluminum hydroxide is added with water to prepare a slurry, and then a phosphorus source is added, followed by spray drying; the solid content of the slurry is 30-40wt%; the molar ratio of the trivalent aluminum source to the phosphorus source is (0.2-0.4): (2.5-2.6). The phosphorus source includes at least one of monoammonium hydrogen phosphate, diammonium hydrogen phosphate, diammonium hydrogen phosphate, and ammonium phosphate.

[0022] In this embodiment, by adopting the above-mentioned feeding method, the titanium aluminum hydroxide and the phosphorus source can be fully mixed, thereby obtaining titanium aluminum phosphate with uniform particle size.

[0023] In some embodiments, the inlet air temperature of the spray drying is 200-350° C., and the discharge temperature is 70-95° C.; and / or the rotation speed of the atomizing wheel is 15000-20000 r / min.

[0024] In this embodiment, the spray drying method can make the phosphorus source evenly coated on the surface of the titanium-aluminum co-precipitate, thereby obtaining a titanium-aluminum-phosphorus mixture with uniform particle size.

[0025] In some embodiments, the calcination process comprises: heating the intermediate product to 600-700° C., keeping the temperature for 6-10 hours, and then cooling down;

[0026] And / or, the heating rate is 2-4°C / min;

[0027] And / or, the cooling rate is 3-6°C / h;

[0028] And / or, the calcination is carried out under the condition that the oxygen volume concentration is 5-15%.

[0029] In this embodiment, the calcination conditions are optimized. Under high temperature calcination conditions, the high temperature accelerates ion diffusion, so that the generated particles have higher density, lower porosity, better sphericity, and smaller BET. The oxygen volume concentration is 5-15%. In an aerobic environment, trivalent titanium can be oxidized to a tetravalent state to ensure the subsequent synthesis of lithium aluminum titanium phosphate materials. At the same time, since titanium and aluminum have formed a coprecipitation, there will be no segregation problem of titanium and aluminum when the valence state of titanium changes.

[0030] In a second aspect, an embodiment of the present application provides aluminum titanium phosphate prepared by the preparation method provided in the first aspect above.

[0031] In this embodiment, the aluminum titanium phosphate material is a spherical particle with a primary particle size of 100-300 nm and a specific surface area of ​​4.0-5.0 m 2 / g, and has a low specific surface area and a small primary particle size.

[0032] In a third aspect, an embodiment of the present application provides a lithium aluminum titanium phosphate electrolyte material, which is prepared using the above-mentioned lithium aluminum titanium phosphate as a precursor.

[0033] In this embodiment, the lithium aluminum titanium phosphate electrolyte material is prepared from the above-mentioned aluminum titanium phosphate, and thus has both a lower specific surface area and a smaller primary particle size.

[0034] In a fourth aspect, an embodiment of the present application provides a lithium-ion battery, wherein the lithium-ion battery comprises the lithium aluminum titanium phosphate electrolyte material as described above.

[0035] In this embodiment, the lithium-ion battery comprises the lithium aluminum titanium phosphate electrolyte material having both a smaller particle size and a lower specific surface area, and thus has high conductivity and good electrochemical stability.

[0036] Compared with the prior art, the beneficial effects of this application include:

[0037] The present invention mixes trivalent aluminum ions and trivalent titanium ions, and then adjusts the pH to perform precipitation reaction, so as to achieve uniform mixing and precipitation of titanium and aluminum, and avoid the segregation problem of aluminum and titanium; the addition of ascorbic acid avoids oxidation of trivalent titanium ions, and further avoids segregation. At the same time, because the solubility product of titanium aluminum hydroxide is very small, a precipitate with a very small primary particle size can be prepared, and then a phosphorus source is spray-coated, and finally aluminum titanium phosphate is synthesized by calcination at high temperature. Compared with the aluminum titanium phosphate precipitate synthesized by the existing liquid phase precipitation method, the primary particle size can be small, and because of the high density, the BET is also relatively small after high-temperature melting, thereby realizing the preparation of products with small BET and small primary particle size.

[0038] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0040] Figure 1 This is a SEM image of the titanium aluminum hydroxide obtained in Example 1 of the present application;

[0041] Figure 2 This is a SEM image of the titanium aluminum phosphate obtained in Example 1 of the present application;

[0042] Figure 3 XRD diagram of lithium aluminum titanium phosphate prepared from the aluminum titanium phosphate of Examples 1 and 2. DETAILED DESCRIPTION

[0043] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0044] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0045] In the description of the embodiments of the present application, “multiple” means more than two, unless otherwise clearly and specifically defined.

[0046] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0047] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0048] The existing methods for synthesizing lithium aluminum titanium phosphate mainly include solid phase sintering method, liquid phase precipitation method and sol-gel method. Among these preparation methods, the solid phase method is simple in process and suitable for industrial mass production. However, it is difficult to obtain a primary particle size of 100-300nm and a BET of 2.5-5.5nm. 2 / g. In order to ensure a smaller BET at a smaller primary particle size, its precursor, titanium aluminum phosphate, is generally required to be spherical particles, and the sizes of the spherical particles are roughly the same. At present, the preparation method of titanium aluminum phosphate precursor is usually a liquid phase precipitation method, for example: adding an aluminum source, a titanium source, and a phosphorus source to water to prepare a mixed salt solution; adding an alkaline solution to the mixed salt solution until the pH value is 7-10 to form a precipitate; or a solid phase sintering method, for example: mixing an aluminum source compound, a phosphorus source compound, and a titanium source compound, then sintering and heat-insulating, and finally pulverizing. Whether it is the current liquid phase precipitation method or the solid phase sintering method, it is ultimately impossible to obtain spherical particles with a small primary particle size, high density, uniform size distribution, and small specific surface area.

[0049] In order to solve the technical problem that the prior art cannot obtain aluminum titanium phosphate with both a small primary particle size and a small specific surface area, the present application provides an aluminum titanium phosphate and a preparation method thereof, and an aluminum titanium phosphate lithium electrolyte material, wherein, by using the above-mentioned aluminum titanium phosphate with both a small primary particle size and a small specific surface area as a precursor material for preparing an aluminum titanium phosphate lithium electrolyte, the primary particle size of the aluminum titanium phosphate lithium electrolyte material can be controlled to be 100-300nm, and the BET is 2.5-5.5m 2 / g, thereby improving the conductivity and cycle stability of lithium-ion batteries.

[0050] In a first aspect, the present invention provides a method for preparing aluminum titanium phosphate, comprising the following steps:

[0051] preparing a mixed solution of a trivalent titanium source, a trivalent aluminum source and ascorbic acid;

[0052] Adjusting the pH of the mixed solution to 6.5-7.5 to obtain titanium aluminum hydroxide;

[0053] The titanium aluminum hydroxide, the phosphorus source and water are mixed and then spray-dried to obtain an intermediate product;

[0054] The intermediate product is calcined to obtain aluminum titanium phosphate.

[0055] Since the precipitation solubility product Ksp of tetravalent titanium ions is particularly small, it is easy to precipitate first. Therefore, in the technical scheme of the embodiment of the present application, trivalent aluminum ions and trivalent titanium ions are mixed. Compared with tetravalent titanium, the Ksp of trivalent titanium ion precipitation is relatively large, the pH of precipitation is higher, and it is easier to form a coprecipitation with trivalent aluminum ions to avoid the segregation problem of titanium; at the same time, ascorbic acid is used as a reducing agent to avoid the oxidation of trivalent titanium ions, further avoid titanium segregation, and obtain a more uniform titanium-aluminum coprecipitation. Because the solubility product of titanium aluminum hydroxide is very small, a precipitate with a very small primary particle size can be prepared, and then spray-coated with a phosphorus source, calcined at high temperature to synthesize aluminum titanium phosphate, compared with the aluminum titanium phosphate precipitate synthesized by the existing liquid phase precipitation method, it can achieve a small primary particle size, and because of the high density, the specific surface area (BET) is also relatively small after high-temperature melting, realizing the preparation of products with small BET and small primary particle size.

[0056] Furthermore, in some embodiments, the trivalent titanium source is one or more of titanium trichloride, titanium sulfate, and titanium oxychloride; the trivalent aluminum source is one or more of aluminum trichloride, aluminum sulfate, and aluminum nitrate; and the molar ratio of the trivalent titanium source, trivalent aluminum source, and ascorbic acid is (1.65-1.75):(0.2-0.4):(0.01-0.05).

[0057] In the technical scheme of the embodiment of the present application, trivalent aluminum ions and trivalent titanium ions are mixed, and the addition of ascorbic acid avoids the oxidation of trivalent titanium ions, which is convenient for controlling the precipitation rate, avoiding the segregation phenomenon, realizing the co-precipitation of titanium and aluminum, and then preparing titanium aluminum hydroxide with a smaller primary particle size. The different ratios of titanium and aluminum affect the ionic conductivity of the subsequent aluminum titanium phosphate. The present application is conducive to preparing an aluminum titanium phosphate lithium product with higher ionic conductivity by limiting the ratio within a reasonable range. If the titanium-aluminum molar ratio exceeds this range, in the case of excessive titanium or excessive aluminum, the ionic conductivity will decrease. In addition, by adopting the above-mentioned ratio range of trivalent titanium source and ascorbic acid, the oxidation of trivalent titanium can be effectively avoided. Excessive ascorbic acid causes waste of resources, and too low an addition amount will not ensure that trivalent titanium is not oxidized during the reaction.

[0058] Further, in some embodiments, alkali solution is added to the mixed solution to adjust the pH of the mixed solution to 6.5-7.5; and / or the temperature of the mixed solution is 40-60° C.; and / or the alkali solution is added for 30-120 min; and / or after the alkali solution is added, the reaction is continued for 30-60 min.

[0059] In the technical scheme of the embodiment of the present application, by controlling the addition conditions of the alkali solution and the coprecipitation reaction conditions, the uniform mixing and precipitation of titanium and aluminum are facilitated, the segregation problem of aluminum and titanium is avoided, and titanium aluminum hydroxide with uniform particle size distribution and high density is obtained. Among them, in the process of adjusting the pH of the mixed solution to 6.5-7.5, if the pH is greater than 7.5, at a higher pH, the precipitation rate of titanium is higher than that of aluminum, which will cause the segregation of titanium; if the pH is less than 6.5, the pH is too low, and the precipitation of aluminum is incomplete, and the appropriate titanium aluminum ratio in the product cannot be guaranteed. The temperature of the precipitation reaction will affect the precipitation reaction rate. If the temperature is too low, the reaction rate is relatively slow. Although the BET is small, there is a problem of large particle size; and if the reaction temperature is too high, although the particle size is small, there is a problem of large BET. The appropriate reaction rate can be controlled within this temperature range, thereby effectively adjusting the BET and particle size of the titanium aluminum hydroxide.

[0060] Furthermore, in some embodiments, the alkali solution includes aqueous ammonia, and the concentration of the aqueous ammonia is 2-4 mol / L.

[0061] The solubility product of the precipitation reaction is small, the solution supersaturation is large, the nucleation rate is too large, and flocculent solids are easily formed, which affects the density and further affects the specific surface area of ​​the product. In the technical scheme of the embodiment of the present application, the addition of ammonia water can act as both a pH regulator and a complexing agent. The ammonia ions in the ammonia water will react with the metal ions in the coprecipitated product to form a precipitate while promoting the formation and stability of the precipitate; at the same time, ammonia water also has the function of a nucleating agent, which reduces the supersaturation and nucleation rate to a certain extent, so that the nucleation rate and the crystal growth rate are in dynamic balance, thereby facilitating the acquisition of titanium aluminum hydroxide with a small primary particle size and high density.

[0062] Furthermore, in some embodiments, the titanium aluminum hydroxide precipitate obtained by co-precipitation is washed with pure water until the conductivity of the washing water is ≤150 μS / cm.

[0063] In the technical solution of the embodiment of the present application, the precipitate is washed with water to remove excess ions in the precipitate that do not participate in the reaction, thereby effectively avoiding the influence of these ions on the final form of subsequent products.

[0064] Furthermore, in some embodiments, the present application also includes mixing the washing water and the mother liquor together, adding ammonia water, adjusting the pH of the solution to 8.5-10, and then filtering, the obtained filtrate is reverse osmosis through an RO membrane, the obtained pure water is returned to the washing precipitate, sulfuric acid is added to the obtained concentrated solution, the pH of the solution is adjusted to 4-5, and ammonium salts, such as ammonium chloride crystals, are obtained through triple-effect evaporation crystallization.

[0065] In the technical solution of the embodiment of the present application, salt recovery is achieved by post-processing the washing water to avoid waste of resources.

[0066] Furthermore, in some embodiments, titanium aluminum hydroxide is added with water to prepare a slurry, and then a phosphorus source is added, followed by spray drying; the solid content of the slurry is 30-40wt%; the molar ratio of the trivalent aluminum source to the phosphorus source is (0.2-0.4): (2.5-2.6). The phosphorus source includes at least one of monoammonium hydrogen phosphate, diammonium hydrogen phosphate, diammonium hydrogen phosphate, and ammonium phosphate.

[0067] In the technical solution of the embodiment of the present application, by adopting the above-mentioned feeding method, the titanium aluminum hydroxide and the phosphorus source can be fully mixed to obtain aluminum titanium phosphate with uniform particle size. By limiting the ratio of metal ions and phosphorus sources within a reasonable range, it is beneficial to control the purity of aluminum titanium phosphate. If the molar ratio is too high, the corresponding phosphorus source content is low, and it is impossible to ensure that the titanium aluminum hydroxide is completely converted into aluminum titanium phosphate; if the molar ratio is too low, the amount of phosphorus source added is too high, resulting in phosphate impurities in the sintered product.

[0068] Furthermore, in some embodiments, the inlet air temperature of the spray drying is 200-350°C, and the outlet temperature is 70-95°C.

[0069] In the technical solution of the embodiment of the present application, the spray drying method realizes the coating structure of the phosphorus source, thereby obtaining a mixture with uniform particle size.

[0070] Further, in some embodiments, the calcination process includes: heating the intermediate product to 600-700°C, keeping it warm for 6-10 hours, and then cooling it; and / or, the heating rate is 2-4°C / min; and / or, the cooling rate is 3-6°C / h; and / or, the calcination is carried out under the condition of an oxygen volume concentration of 5-15%.

[0071] In the technical solution of the embodiment of the present application, different sintering temperatures will affect the BET and particle size of the final titanium aluminum phosphate. If the sintering temperature is too low, the BET is large; if the sintering temperature is too high, although the BET is small, the particles melt with each other during the high-temperature solid-phase reaction, resulting in a large particle size that is difficult to crush. The introduction of oxygen can oxidize trivalent titanium to a tetravalent state at this stage to ensure the subsequent synthesis of lithium titanium aluminum phosphate materials. At the same time, since titanium and aluminum have formed a co-precipitation, there will be no segregation problem of titanium and aluminum when the valence state of titanium changes.

[0072] In a second aspect, an embodiment of the present application provides a titanium aluminum phosphate, which is prepared by the preparation method provided by the first aspect above.

[0073] The aluminum titanium phosphate material is a spherical particle with a primary particle size of 100-300nm and a specific surface area of ​​4.0-5.0m 2 / g, and has a low specific surface area and a small primary particle size.

[0074] In a third aspect, an embodiment of the present application provides a lithium aluminum titanium phosphate electrolyte material, which is prepared using the above-mentioned lithium aluminum titanium phosphate as a precursor.

[0075] In the technical solution of the embodiment of the present application, the lithium aluminum titanium phosphate electrolyte material is prepared from the above-mentioned aluminum titanium phosphate, and thus has both a lower specific surface area and a smaller primary particle size.

[0076] In a fourth aspect, an embodiment of the present application provides a lithium-ion battery, wherein the lithium-ion battery comprises the lithium aluminum titanium phosphate electrolyte material as described in the third aspect above.

[0077] In the technical solution of the embodiment of the present application, the lithium-ion battery contains the above-mentioned lithium aluminum titanium phosphate electrolyte material, and thus has high conductivity and good electrochemical stability.

[0078] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.

[0079] Example 1

[0080] (1) Add titanium trichloride and aluminum trichloride into pure water to dissolve to obtain a titanium-aluminum mixed solution, then add ascorbic acid and stir until completely dissolved; the molar ratio of aluminum trichloride, titanium trichloride and ascorbic acid is 0.3:1.7:0.025.

[0081] (2) adding aqueous ammonia to the mixed solution to carry out a precipitation reaction, and filtering to obtain a titanium aluminum hydroxide co-precipitate; the concentration of the aqueous ammonia is 3 mol / L, and the pH of the solution is adjusted to 7 by adding aqueous ammonia. The time for adding aqueous ammonia is 60 minutes, and then the reaction is continued with stirring for 50 minutes. The reaction temperature is maintained at 50°C during the whole process.

[0082] (3) The titanium aluminum hydroxide coprecipitate is washed with pure water until the conductivity of the washing water reaches 135 μS / cm, and then the washing is stopped. Pure water is added to the washed titanium aluminum hydroxide to slurry it, and then ammonium monohydrogen phosphate is added, and then spray drying is performed to obtain a spray-dried material; the molar ratio of aluminum trichloride to ammonium monohydrogen phosphate is 0.3:2.57; during the slurrying process, the solid content is 35wt%, and after adding ammonium monohydrogen phosphate, the slurry is heated to 70°C. During the spray drying process, the speed of the atomizing wheel is adjusted to 18000r / min, the air inlet temperature is 300°C, and the discharge temperature is 85°C.

[0083] (4) The spray-dried material is placed in a tubular furnace and calcined to obtain aluminum titanium phosphate. During the calcination process, the temperature is raised at a rate of 3°C / min to a temperature of 650°C, which is kept at this temperature for 8 hours, and then cooled at a rate of 4.5°C / h. During the calcination process, an inert atmosphere (nitrogen) with an oxygen volume concentration of 9.5% is introduced. After cooling, the material taken out of the furnace is sieved and iron removed before packaging. A 250-mesh sieve is used for sieving to obtain aluminum titanium phosphate.

[0084] After the washing water and the mother liquor are mixed together, ammonia water is added to adjust the pH of the solution to 9, and then filtered. The obtained filtrate is reverse osmosis through an RO membrane, and the obtained pure water is returned to wash the precipitate. Sulfuric acid is added to the obtained concentrate to adjust the pH of the solution to 4.5, and ammonium chloride crystals are obtained after triple evaporation and crystallization. The final purity of ammonium chloride is 98.7%.

[0085] Example 2

[0086] The preparation steps of Example 2 differ from those of Example 1 in that ammonia water is added in step (2) to adjust the pH of the solution to 7.5. Specifically, (1) titanium trichloride and aluminum trichloride are added to pure water to dissolve to obtain a titanium-aluminum mixed solution, and then ascorbic acid is added and stirred until completely dissolved; the molar ratio of aluminum trichloride, titanium trichloride and ascorbic acid is 0.3:1.7:0.025.

[0087] (2) adding ammonia water to the above mixed solution to carry out precipitation reaction, and filtering to obtain titanium aluminum hydroxide co-precipitate; the concentration of ammonia water is 3 mol / L, and ammonia water is added to adjust the pH of the solution to 7.5. The time of adding ammonia water is 60 minutes, and then the stirring reaction is continued for 50 minutes. The reaction temperature is maintained at 50°C during the whole process.

[0088] (3) The titanium aluminum hydroxide coprecipitate is washed with pure water until the conductivity of the washing water reaches 135 μS / cm, and then the washing is stopped. Pure water is added to the washed titanium aluminum hydroxide to slurry it, and then ammonium monohydrogen phosphate is added, and then spray drying is performed to obtain a spray-dried material; the molar ratio of aluminum trichloride to ammonium monohydrogen phosphate is 0.3:2.57; during the slurrying process, the solid content is 35wt%, and after adding ammonium monohydrogen phosphate, the slurry is heated to 70°C. During the spray drying process, the speed of the atomizing wheel is adjusted to 18000r / min, the air inlet temperature is 300°C, and the discharge temperature is 85°C.

[0089] (4) The spray-dried material is placed in a tubular furnace and calcined to obtain aluminum titanium phosphate. During the calcination process, the temperature is raised at a rate of 3°C / min to a temperature of 650°C, which is kept at this temperature for 8 hours, and then cooled at a rate of 4.5°C / h. During the calcination process, an inert atmosphere (nitrogen) with an oxygen volume concentration of 9.5% is introduced. After cooling, the material taken out of the furnace is sieved and iron removed before packaging. A 250-mesh sieve is used for sieving to obtain aluminum titanium phosphate.

[0090] Example 3

[0091] The difference between the preparation steps of Example 3 and Example 1 is that in step (2), ammonia water is added to adjust the pH of the solution to 6.5. The remaining preparation steps are the same as those of Example 1 to obtain aluminum titanium phosphate.

[0092] Example 4

[0093] The difference between the preparation steps of Example 4 and Example 1 is that in step (4), the calcination temperature is 600° C. Specifically:

[0094] (1) Add titanium trichloride and aluminum trichloride into pure water to dissolve to obtain a titanium-aluminum mixed solution, then add ascorbic acid and stir until completely dissolved; the molar ratio of aluminum trichloride, titanium trichloride and ascorbic acid is 0.3:1.7:0.025.

[0095] (2) adding aqueous ammonia to the mixed solution to carry out a precipitation reaction, and filtering to obtain a titanium aluminum hydroxide co-precipitate; the concentration of the aqueous ammonia is 3 mol / L, and the pH of the solution is adjusted to 7 by adding aqueous ammonia. The time for adding aqueous ammonia is 60 minutes, and then the reaction is continued with stirring for 50 minutes. The reaction temperature is maintained at 50°C during the whole process.

[0096] (3) The titanium aluminum hydroxide coprecipitate is washed with pure water until the conductivity of the washing water reaches 135 μS / cm, and then the washing is stopped. Pure water is added to the washed titanium aluminum hydroxide to slurry it, and then ammonium monohydrogen phosphate is added, and then spray drying is performed to obtain a spray-dried material; the molar ratio of aluminum trichloride to ammonium monohydrogen phosphate is 0.3:2.57; during the slurrying process, the solid content is 35wt%, and after adding ammonium monohydrogen phosphate, the slurry is heated to 70°C. During the spray drying process, the speed of the atomizing wheel is adjusted to 18000r / min, the air inlet temperature is 300°C, and the discharge temperature is 85°C.

[0097] (4) The spray-dried material is placed in a tubular furnace and calcined to obtain aluminum titanium phosphate. During the calcination process, the temperature is raised at a rate of 3°C / min to 600°C, kept at this temperature for 8 hours, and then cooled at a rate of 4.5°C / h. During the calcination process, an inert atmosphere (nitrogen) with an oxygen volume concentration of 9.5% is introduced. After cooling, the material taken out of the furnace is sieved and iron removed before packaging. The sieve is sieved using a 250-mesh sieve to obtain aluminum titanium phosphate.

[0098] Example 5

[0099] The difference between the preparation steps of Example 5 and Example 1 is that in step (4), the calcination temperature is 700° C. The remaining preparation steps are the same as those of Example 1 to obtain aluminum titanium phosphate.

[0100] Comparative Example 1

[0101] Aluminum titanium phosphate is prepared by liquid phase precipitation method, the steps are as follows:

[0102] Titanyl sulfate, aluminum sulfate, sodium hydroxide and sodium dihydrogen phosphate were prepared into 1 mol / L solutions respectively, and then added into the reactor together for stirring reaction. The pH of the process was maintained at 4.5, the reaction temperature was 50°C, the feeding time was 45 minutes, and the reaction was continued for 60 minutes. After filtering, washing and drying, titanium aluminum phosphate was obtained.

[0103] Performance testing and analysis

[0104] 1. Test Method

[0105] 1. After washing and vacuum drying the titanium aluminum hydroxide precipitate obtained in step (2) of Example 1, its element content, specific surface area, pH, particle size and tap density were detected. Among them, the element content was tested by inductively coupled plasma emission spectrometer (ICP), the specific surface area was tested by nitrogen adsorption BET test method, reference standard GB / T 19587 2017; the tap density was tested by tap density meter, reference standard GB / T 5162 2021; the pH test method was: 10g of material, 100g of pure water, stirred for 30min, and then the pH was measured at a temperature of 25°C; the particle size was tested by laser particle size analyzer, and the test results are shown in Table 1.

[0106] 2. The structures of the titanium aluminum hydroxide precipitate and aluminum titanium phosphate prepared in Example 1 were observed by scanning electron microscopy, and the following were obtained: Figure 1 and Figure 2 SEM images shown.

[0107] 3. Detect the element content, specific surface area, particle size, tap density and magnetic material content of titanium aluminum phosphate in Examples 1 to 5 and Comparative Example 1. The element content, specific surface area, particle size, tap density and magnetic material content are the same as those of titanium aluminum hydroxide precipitation. The detection method of magnetic material is as follows: take 100g of material, add 1000g of alcohol, then add it to a PE bottle, then add it to a magnetic bar covered with a polytetrafluoroethylene jacket, the magnetic field strength of the magnetic bar is 12000GS, then place the PE bottle horizontally, and rotate the PE bottle. After rotating for 30 minutes, take out the magnetic bar, rinse it with pure water, and dissolve it with acid to completely dissolve the material adsorbed in the magnetic bar, and then ICP measures the sum of nickel, chromium, copper, zinc and iron therein, which is the magnetic material. The test results are shown in Table 2.

[0108] 4. The aluminum titanium phosphate prepared in Example 1 of the present invention was mixed with lithium carbonate in a molar ratio of lithium:titanium = 1.3:1.7, and sintered at 750° C. for 12 h to obtain lithium aluminum titanium phosphate, and its XRD was tested.

[0109] 2. Test Results

[0110] Table 1 Detection data of titanium aluminum hydroxide in Example 1

[0111] index Ti Al BET pH Tap density data 38.01% 4.31% <![CDATA[19.7m 2 / g]]> 10.9 0.78g / mL D10 D50 D90 Ca Mg Na 0.2μm 1.2μm 5.8μm 25.8ppm 45.1ppm 26.8ppm Cu Zn Ni Pb Cr Mn 0.4ppm 4.7ppm 3.7ppm 0.3ppm 1.6ppm 37.4ppm

[0112] Figure 1 This is a SEM image of the titanium aluminum hydroxide prepared in Example 1 of the present invention. Figure 1 It can be seen that titanium aluminum hydroxide is a fluffy particle, which has high reactivity and can be easily carried out in the next step of solid phase calcination. At the same time, the granular structure is convenient for washing, avoiding the problem of a large amount of impurities entrained by floccules.

[0113] Table 2 Test data of the embodiment and comparative example aluminum titanium phosphate

[0114]

[0115]

[0116] It can be seen from Table 2 that the specific surface area and particle size of the aluminum titanium phosphate prepared in the embodiment of the present invention are relatively small.

[0117] Figure 2 This is a SEM image of aluminum titanium phosphate prepared in Example 1 of the present invention. Figure 2 It can be seen that aluminum titanium phosphate is a spherical particle with a relatively smooth particle surface and a small specific surface area; the primary particle size distribution is relatively uniform, the dispersibility is good, and the primary particle size is about 100-300nm. This shows that the method of the present invention is conducive to the preparation of aluminum titanium phosphate with good dispersibility, small and uniform primary particle size, and small specific surface area.

[0118] It can be seen from the comparison between Comparative Example 1 and Example 1 that the process of the present invention can be used to prepare a material with a small BET, a high degree of density, a concentrated particle size distribution, and a small particle size.

[0119] Figure 3 The XRD diagram of lithium aluminum titanium phosphate prepared from the aluminum titanium phosphate of Examples 1 and 2 shows that the product is a relatively pure phase lithium aluminum titanium phosphate material.

[0120] The aluminum titanium phosphate lithium material prepared from the aluminum titanium phosphate of Example 1 was made into a material with a thickness of 0.16 cm and an area of ​​0.785 cm 2 The electrolyte sheet was tested by AC internal resistance tester. The aluminum titanium lithium phosphate material has low internal resistance and high ionic conductivity. The resistance is 5663Ω and the ionic conductivity is 3.60×10 -5 S / cm.

[0121] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A method for preparing aluminum titanium phosphate, characterized in that: The following steps are involved: A mixed solution of a trivalent titanium source, a trivalent aluminum source and ascorbic acid is prepared; the molar ratio of the trivalent titanium source, the trivalent aluminum source and the ascorbic acid is (1.65-1.75): (0.2-0.4): (0.01-0.05); Adding ammonia water to the mixed solution to adjust the pH of the mixed solution to 6.5-7.5, and controlling the temperature of the mixed solution to 40-60° C., the adding time of the ammonia water is 30-120 min, and after the addition of the ammonia water is completed, continuing the reaction for 30-60 min to obtain titanium aluminum hydroxide; Washing the titanium aluminum hydroxide until the conductivity of the washing water is ≤150 μS / cm; The titanium aluminum hydroxide, phosphorus source and water are mixed and then spray-dried to obtain an intermediate product; Under the condition of oxygen volume concentration of 5-15%, the intermediate product is heated to 600-700° C. for calcination to obtain aluminum titanium phosphate.

2. The preparation method according to claim 1, characterized in that: The trivalent titanium source is one or more of titanium trichloride, titanium sulfate, and titanium oxychloride; and / or The trivalent aluminum source is one or more of aluminum trichloride, aluminum sulfate, and aluminum nitrate.

3. The preparation method according to claim 1, characterized in that: Adding water to the titanium aluminum hydroxide to prepare a slurry, adding a phosphorus source, and then spray drying; and / or The solid content of the slurry is 30-40wt%; and / or The phosphorus source comprises at least one of monoammonium hydrogen phosphate, diammonium hydrogen phosphate, diammonium hydrogen phosphate, and ammonium phosphate; and / or The molar ratio of the trivalent aluminum source to the phosphorus source is (0.2-0.4): (2.5-2.6).

4. The preparation method according to claim 1, characterized in that: The inlet air temperature of the spray drying is 200-350°C, and the outlet temperature is 70-95°C.

5. The preparation method according to claim 1, characterized in that: The calcination process comprises: heating the intermediate product to 600-700° C., keeping the temperature for 6-10 hours, and then cooling down; And / or, the heating rate is 2-4°C / min; And / or, the cooling rate is 3-6°C / h.

6. Aluminum titanium phosphate obtained according to the preparation method according to any one of claims 1 to 5.

7. A lithium aluminum titanium phosphate electrolyte material, characterized in that: The titanium aluminum phosphate according to claim 6 is used as a precursor.

8. A lithium ion battery, characterized in that: The lithium-ion battery comprises the lithium titanium aluminum phosphate electrolyte material as claimed in claim 7.

Citation Information

Patent Citations

  • Modified lithium iron manganese phosphate positive electrode material, preparation method thereof and lithium ion battery

    CN116632191A

  • Preparation method of high-performance LATP solid electrolyte

    CN117766849A